Reframing the Frontier: Religion, Race, and Colonial Violence in American Primeval (2025) - Alfira Khairina Intifadah; Krisna Sujiwa; Yusrina Dinar Prihatika (Universitas Islam Negeri Palopo, 2025)
The American frontier has long been celebrated as a narrative of progress and divine destiny, yet this myth conceals the colonial violence and religious extremism that shaped U.S. expansion. This study investigates how the Netflix miniseries American Primeval (2025) deconstructs that mythology by exposing the intersections of religion, race, and power within nineteenth-century Mormon expansion. Drawing on Mohrman’s (2022) analysis of how religious ideologies intensify settler colonial violence, this research examines how American Primeval portrays faith not as salvation but as an instrument of domination. Using qualitative content analysis and guided by settler colonial theory, the study analyzes selected episodes (2–5) focusing on dialogues, character arcs, and visual framing that reveal how spiritual conviction was weaponized to justify land seizure, racial hierarchy, and intra-settler violence. The findings show that the series reframes Mormonism as both a faith of refuge and a mechanism of control—demonstrating how the pursuit of Zion transformed into the reproduction of colonial systems. By foregrounding Indigenous resistance and exposing the moral contradictions of frontier religiosity, American Primeval challenges the enduring myth of American exceptionalism. Addressing the research gap in the representation of Mormon expansion within contemporary visual media, this study contributes to scholarship on settler colonialism by illustrating how screen narratives can revise historical memory and critique the theological foundations of conquest. Ultimately, the series serves as a cinematic act of historical revision that reclaims the frontier as a site of trauma, resistance, and moral reckoning.